A novel objective method for deceased donor and recipient size matching in liver transplantation. Issue 12 (6th November 2015) - Croome, Kristopher P.; Lee, David D.; Saucedo‐Crespo, Hector; Burns, Justin M.; Nguyen, Justin H.; Perry, Dana K.; Taner, C. Burcin
Abstract : Although the consequences of implantation of a large whole liver graft into a small recipient such as compression and compromise of graft perfusion are well known, no accepted measure to aid in donor‐to‐recipient size matching exists. Donor liver graft and recipient native liver weights as well as donor and recipient size and amount of ascites were investigated in 1953 patients who underwent liver transplantation using deceased donor grafts between January 2002 and July 2013. We used a previously described formula for liver resections (standardized total liver volume [sTLV] = –794.41 + 1267.28 × body surface area [m 2 ]) for calculating sTLV, in the current cohort of deceased liver donors. Early allograft dysfunction (EAD) and graft survival were the primary outcome measures. The formula for calculating sTLV for liver resections was validated as an accurate predictor of liver volume in the current cohort of deceased liver donors ( r 2  = 0.45; P  < 0.001). A cutoff point of sTLV ratio ≥ 1.25 was determined through receiver operating characteristic curves, and patients were dichotomized into 2 groups. In the sTLV ratio ≥ 1.25 group, 50% of patients developed EAD compared to 25% of patients in the sTLV ratio < 1.25 group ( P  < 0.001). The proportion of patients developing graft failure within 90 days was 9.6% in the sTLV ratio ≥ 1.25 group and 5.4% in the sTLV ratio < 1.25 group ( P  = 0.045). This study validates the use of the sTLV for prediction of actual donor liver weight in the transplant setting. Using this formula, donors with a calculated sTLV size ratio ≥ 1.25 have an increased risk of EAD and therefore caution should be used when that value is exceeded. This adjusted size ratio can be used as a decision aid when considering donor and recipient matching with potential liver organ offers. Liver Transpl 21:1471‐1477, 2015 . © 2015 AASLD.